Nongenomic steroid actions: fact or fantasy - Christ, Michael; Rossol-Haseroth, Karin; Falkenstein, Elisabeth; Wehling, Martin (Vitamins and hormones, 1997)
In the common theory of steroid action, steroids bind to intracellular receptors and modulate nuclear transcription after translocation of steroid-receptor complexes into the nucleus. Due to homologies of molecular structure, specific receptors for steroids, vitamin D3, and thyroid hormone are considered to represent a superfamily of steroid receptors. While genomic steroid effects being characterized by their delayed onset of action and their sensitivity to blockers of transcription and protein synthesis have been known for several decades, very rapid actions of steroids have been more widely recognized and characterized in detail only recently. Rapid effects of steroids, vitamin D3, and thyroid hormones on cellular signaling and function may be transmitted by specific membrane receptors. Although no receptor of this kind has been cloned up to now, binding sites in membranes have been characterized exposing binding features compatible with an involvement in rapid steroid signaling. Characteristics of putative membrane receptors were completely different from those of intracellular steroid receptors, which was further supported by the inability of classic steroid receptor antagonists to inhibit nongenomic steroid actions. Development of drugs that specifically affect nongenomic action alone or even both modes of actions may find applications in various areas such as the cardiovascular and central nervous systems and treatment of preterm labor, infertility, and electrolyte homeostasis. To acquaint the reader with major aspects of nongenomic steroid actions, these effects on cellular function will be summarized, potentially related binding sites in membranes discussed, and the physiological or pathophysiological relevance of nonclassic actions exemplified.